The impact of COVID-19 on mental health and posttraumatic growth of Korean college students: a mixed method study examining the moderating role of coping flexibility and sense of community - Sim, Jae-Chang; Im, Sun-Young (Frontiers in Psychology, 2023)
This study was divided into two parts. The first study used a quantitative research method to test if coping flexibility and sense of community moderated the impact of COVID-19-related concerns on mental health (i.e., depression and anxiety) and posttraumatic growth among Korean college students. The second study used a qualitative research method for an in-depth examination of how Korean college students coped with the COVID-19 pandemic and if they achieved any positive change or growth. Given that the COVID-19 pandemic represents a situation distinct from what people have previously encountered, Study II was designed to examine the experiences of individuals during this exceptional period. In the first study (Study I), coping flexibility was found to increase the impact of COVID-19-related concerns and difficulties on depression and anxiety. Conversely, a sense of community reduced the consequences of these overwhelming worries on depression and anxiety, while also expanding the impact of COVID-19-related disorders on posttraumatic growth. In the second study (Study II), the findings showed that the participants experienced various psychological consequences, including depression and anxiety, and distress in other aspects of their life, including disruptions in interpersonal relationships and college life. Nonetheless, the participants made efforts to cope with such difficulties and overcome the challenges together with the community. In fact, the pandemic improved their coping skills and expanded their value system and worldview. The study findings suggest that given the unique situation presented by the COVID-19 pandemic, a sense of community protected the mental well-being of Korean college students and facilitated their growth.